Divine Freedom and Free Will Defenses - Franks, W. Paul (Heythrop journal, 2015)
This paper considers a problem that arises for free will defenses when considering the nature of God's own will. If God is perfectly good and performs praiseworthy actions, but is unable to do evil, then why must humans have the ability to do evil in order to perform such actions? This problem has been addressed by Theodore Guleserian, but at the expense of denying God's essential goodness. I examine and critique his argument and provide a solution to the initial problem that does not require abandoning God's essential goodness.